2000
DOI: 10.2527/2000.7871936x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cortisol and ACTH concentrations in the warmblood horse in response to a standardized treadmill exercise test as physiological markers for evaluation of training status.

Abstract: Reliable physiological markers for performance evaluation in sport horses are missing. To determine the diagnostic value of plasma ACTH and cortisol measurements in the warmblood horse, 10 initially 3-yr-old geldings of the Hannovarian breed were either exposed to a training schedule or served as controls. During experimental Phase 1, horses were group-housed, and half of the horses were trained for 20 wk on a high-speed treadmill. During Phase 2, groups were switched and one group was trained for 10 wk as dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 0 publications
5
44
1
9
Order By: Relevance
“…Exercise leads to an increase in cortisol, in humans as well as in horses [19][20][21][22][23][24]. However, by taking saliva samples during a board game competition in Japan, researchers found that changes in salivary cortisol after competition are associated with winning and losing, even if this game does not need physical exercise [25].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise leads to an increase in cortisol, in humans as well as in horses [19][20][21][22][23][24]. However, by taking saliva samples during a board game competition in Japan, researchers found that changes in salivary cortisol after competition are associated with winning and losing, even if this game does not need physical exercise [25].…”
Section: Introductionmentioning
confidence: 99%
“…Os valores de cortisol sérico registrados na presente pesquisa em todos os momentos de avaliação são superiores aos descritos por Marc et al (2000) e Dugat et al (2010), sendo semelhantes aos de Williams et al (2000) somente nos momentos antes e com duas horas após o término do exercício físico. Corroborando com o trabalho de Gordon et al (2007) e Islas et al (2007), os maiores valores na presente pesquisa foram registrados entre 5 e 30 minutos após o término da atividade física, justificando tal fato como resposta aguda frente ao estresse.…”
Section: Discussionunclassified
“…Segundo Hyyppä (2005), sua principal função é prover a biodisponibilidade dos precursores energéticos necessários para manter os esforços musculares através de diversas vias de ação, dentre as quais degradação de proteínas teciduais para liberação de aminoácidos usados na gliconeogênese hepática, mobilização de ácidos graxos livres do tecido adiposo e redução da taxa de utilização celular de glicose. No repouso, Marc et al (2000) citaram intervalo de valores entre 1,47 e 6,73mg/dL e Williams et al (2002) descreveram valores entre 4,5 e 7,5mg/dL. Trabalho mais recente de Dugat et al (2010) cita valores oscilando entre 2,9 e 6,6mg/dL.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Respiratory rate and blood lactate are the most sensitive physiological parameters indicating training status (MARC et al, 2000). Lactate metabolism is linked Hematologic and biochemical parameters in three high performance horse breeds from Southern Brazil to glucose metabolism (KANEKO et al, 1997).…”
Section: Discussionmentioning
confidence: 99%